Inovasi Pemberdayaan Kader untuk Cegah Stunting - Mahdiah Mahdiah; Ratna Zahara (Jurnal Pengabdian Gizi dan Kesehatan Masyarakat, 2026)
ABSTRACT This community service program was carried out to prevent stunting through cadre empowerment and nutrition education for pregnant and breastfeeding mothers in Tanjung Selamat Village, Deli Serdang Regency. The purpose of this activity was to improve knowledge, attitudes, and skills in utilizing Sukahitu premix flour as a local food innovation for stunting prevention. The methods included lectures, interactive discussions, educational video presentations, and demonstrations of snack preparation using Sukahitu premix flour. The activity involved 33 participants consisting of cadres, pregnant women, and breastfeeding mothers. The results showed an increase in knowledge, with the proportion of participants in the good category rising from 39.4% before education to 90.9% after education. Positive attitudes increased from 78.8% to 100%. Statistical analysis confirmed that education had a significant effect on improving knowledge (p=0.001) and attitudes (p=0.001). In conclusion, cadre empowerment through nutrition education and demonstrations using Sukahitu premix flour was effective in enhancing community capacity and has the potential to serve as a sustainable strategy for stunting prevention at the village level.